Electrochemical Red Blood Cell Counting: One at a Time. Issue 33 (29th June 2016) - Sepunaru, Lior; Sokolov, Stanislav V.; Holter, Jennifer; Young, Neil P.; Compton, Richard G.
Abstract: We demonstrate that the concentration of a red blood cell solution under physiological conditions can be determined by electrochemical voltammetry. The magnitude of the oxygen reduction currents produced at an edge‐plane pyrolytic graphite electrode was diagnosed analytically at concentrations suitable for a point‐of‐care test device. The currents could be further enhanced when the solution of red blood cells was exposed to hydrogen peroxide. We show that the enhanced signal can be used to detect red blood cells at a single entity level. The method presented relies on the catalytic activity of red blood cells towards hydrogen peroxide and on surface‐induced haemolysis. Each single cell activity is expressed as current spikes decaying within a few seconds back to the background current. The frequency of such current spikes is proportional to the concentration of cells in solution. Abstract : Catalytically active red blood cells : With the use of a nano‐electrochemical technique fast and accurate red blood cell counting can be achieved together with complementary informations regarding the cell activity from each single cell. The method relies on the catalytic activity of red blood cells towards hydrogen peroxide and on surface‐induced haemolysis.